Acid corrosion behaviour of Ti–48Al–6Nb porous alloys with different phase skeletons. (18th May 2016) - Wang, F.; Liang, Y. F.; Jin, X. O.; Lin, J. P.
Abstract : Ti–48Al–6Nb porous alloys with different phase skeletons were synthesised by powder metallurgy at different temperatures. TiAl3 skeletons achieved at 700°C were covered by corrosion products and skeletons fractures led to pores collapse. TiAl skeletons were synthesised at 900°C with obvious corrosion pits and pore diameter increasing. And Ti3 Al/TiAl skeletons achieved at 1350°C exhibit the best acid corrosion resistance with the least mass loss of 1.853 mg m –2 . Skeletons and pore diameters remained stable just with fully lamellar structures emerged. In addition, Nb2 Al phases presented better resistance than NbAl3 in the skeletons contributing to acid corrosion resistance of the porous alloys.